Teaching Statistics with Current and Historical Events: An Analysis of Survivor Data From the Sinking of the HMT Birkenhead, the RMS Titanic, and the Korean Ferry MV Sewol - Lee, Young; Schumm, Walter R.; Lockett, Lorenza; Newsom, Kimmery C.; Behan, Kathleen (My University, 2016)
Statistical examples can feel remote to students, especially if the variables under consideration are ambiguous. However, life or death is not ambiguous but very concrete. Three different historical shipwrecks offer an abundance of ways to demonstrate the relevance and importance of statistics. Here, we discuss statistical outcomes associated with the loss of three ships: the HMT Birkenhead in 1852, the RMS Titanic in 1912, and the Korean ferry MV Sewol in April 2014. These disasters can serve as examples for demonstrating the relevance of statistics to current events. Statistics in these historical events can help students see that the survival rates of different groups of passengers were very different, with medium to large effect sizes. Even if statistical analyses cannot answer all of the questions about why some passengers had higher survival rates than others, they can lead to further productive qualitative or quantitative research into such questions.
Citation: Lee, Y., Schumm, W. R., Lockett, L., Newsom, K. C., & Behan, K. (2016). Teaching Statistics with Current and Historical Events: An Analysis of Survivor Data From the Sinking of the HMT Birkenhead, the RMS Titanic, and the Korean Ferry MV Sewol. Comprehensive Psychology, 5, 216522281664790. https://doi.org/10.1177/2165222816647900
Keywords: research methodology; naval disasters; survival rates; RMS Titanic; HMT Birkenhead; MV Sewol